Origin and Paleoenvironmental Significance of the Old Red Sand Along the Southeast Coast of China - Fan, Qingbin; Liao, Jie; Li, Yan; Ye, Wei; Wang, Tao; Feng, Xiao (Frontiers in Earth Science, 2021)
The “Old Red Sand” (ORS) along the southeast coast of China is of significant paleoclimatic and paleoenvironmental significance. However, its provenance remains controversial. In this study, grain size characteristics and quartz grain surface microtextures were analyzed to study the origin and paleoenvironmental significance of the ORS, the results show that the ORS show typical aeolian features and subaqueous environments characteristics, combined with the latest OSL dating data, we suggest that the ORS should be coastal aeolian sand dunes developed since the last interglacial period. The formation of the ORS was restricted jointly by climate changes of the coastal area and the distance from the shoreline that resulted from sea level changes.